2019
DOI: 10.3389/fnins.2019.01211
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Elapsed Time and Decision Accuracy Differs Between Humans and Rats

Abstract: A stochastic visual motion discrimination task is widely used to study rapid decision-making in humans and animals. Among trials of the same sensory difficulty within a block of fixed decision strategy, humans and monkeys are widely reported to make more errors in the individual trials with longer reaction times. This finding has posed a challenge for the drift-diffusion model of sensory decision-making, which in its basic form predicts that errors and correct responses should have the same reaction time distr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…Finally, we validated our interpretation of the GLM-HMM’s latent states when we compared the response times and violation rates (quantities not used to fit our model) associated with engaged and disengaged states. We found that the most extreme response times were typically associated with the disengaged states, which is consistent with previous findings linking accuracy and response times [32, 53, 61]. Taken together, these results shed substantial new light on the factors governing sensory decision-making in rodents, and provide a powerful set of tools for identifying hidden states in behavioral data.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, we validated our interpretation of the GLM-HMM’s latent states when we compared the response times and violation rates (quantities not used to fit our model) associated with engaged and disengaged states. We found that the most extreme response times were typically associated with the disengaged states, which is consistent with previous findings linking accuracy and response times [32, 53, 61]. Taken together, these results shed substantial new light on the factors governing sensory decision-making in rodents, and provide a powerful set of tools for identifying hidden states in behavioral data.…”
Section: Introductionsupporting
confidence: 90%
“…Previous literature has revealed that humans and monkeys commit more errors on long duration trials than short duration trials [32, 53, 61]. We, thus, looked at the distributions of response times for the engaged state, compared to for the disengaged states (the biased left and biased right states), for mice performing the IBL task.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We noticed with surprise that some rats in a previous study (10) had longer mean response times to easier random dot motion stimuli (Figure 1 E,F), in spite of having unremarkable psychometric curves with minimal lapse (Figure 1A,B, performance at high coherence near 100%). Other rats in the same cohort with comparable psychometric curves (Figure 1 The inverted chronometric response functions were attributable mostly to the correct trials (Figure 2 A,B green; c.f.…”
Section: Resultsmentioning
confidence: 75%
“…No new experiments are reported in this paper; the data are from a previous publication (10) and the previously unpublished supplemental video is from (2). Those studies were both performed in full accordance with ethical guidelines for animal research, as approved and overseen by the UCSD IACUC.…”
Section: Methodsmentioning
confidence: 99%